Development of underwater glider system model using two stage identification approach. - Aziz, Muhammad Hilmi R. (Asean Engineering Journal)
This paper presents mathematical models for a new hull shape underwater glider system developed by Underwater Robotics Research Group, USM. Mathematical model of this glider system is first developed in order to provide a model based control to the system. To obtain the model of the system, two stages identification have been used in the identification process. First stage utilizes the use of frequency sampling filters to compress the data and obtain meaningful parameter that describes the empirical model of the system. This stage is required since data acquisition from glider system yields large amount of data and it may lead to a long computational time in the identification process. The information of the empirical model will be used for the second step, in which, the continuous time subspace method will be used to obtain the state space model of the system. At this stage, two familiar subspace methods those are MOESP and ORT have been used in order to obtain optimized model of the glider system. Three performance evaluation tests according to mean square error, variance accounted for and best fit are used to verify the accuracy of the developed models.